When science, politics, and policy collide: On the regulation of anabolic-androgenic steroids, steroid precursors, and "Dietary supplements" in the United States - Denham, B. E. (Journal of Sport and Social Issues, 2011)
Twenty years after policy makers passed the Anabolic Steroid Control Act of 1990, adding steroids to the list of Schedule III Controlled Substances in the United States, illicit use of the drugs continues among both adolescents and adults in American society. Some of the men and women who use steroids seek enhanced athletic performance, whereas others simply want to appear more muscular. But what, exactly, is a "steroid"? The present article examines legislation surrounding actual anabolic-androgenic steroids, steroid precursors, and associated "dietary supplements," exploring how the political interests of policy actors and the economic interests of industry lobbies have compromised regulatory efforts. Among the issues addressed are the arbitrary assignment of substances to (and exemption from) the Omnibus Controlled Substances Act and the retailing of "dietary supplements" that contain widely varying amounts of active ingredients and, in some cases, synthetic steroids. Conceptually, the article draws on the "garbage can" model of policy processes as well as the broader public arenas model of social problems, focusing on subjective issue constructions and symbolic appeals.